Study of Hepatic Dysfunction in Patientsinfected with Dengue Virus - Younus, M; Ejaz, Aiysha; Khan, Mutti-ur-Rehman; Maqbool, Azhar; Qamar-un-Nisa; Raza, Sanan; Khan, Aman Ullah (Journal of Diagnostics, 2015)
Dengue fever is a fatal infection affecting the lives of the patients and this study was designed to further explore its pathological effects. A total of 200 consecutives of dengue viral infection were included in this prospective descriptive study conducted at the Department of Pathology, University of Veterinary and Animal Sciences, Lahore from October, 2009 to September, 2010. A special proforma was designed to collect all the relevant clinical information from each patient. All the strip positive cases of dengue virus were further confirmed by performing IgM capture ELISA and then analyzed for hepatic impairment through liver function tests including serum bilirubin, serum alkaline phosphatase, serum ALT and AST. The results were then gathered and analyzed. The already existing liver diseases like hepatitis A, B, C, E and inherited liver disorders were not included in the study. Total number of patients included in study with Dengue IgM +ve were 200. Out of 200 cases 130 were male and 70 were females. The patients were categorized into two classes according to severity of sign symptoms like puerperal rash on the body. The classes are dengue fever (DF) and dengue hemorrhagic fever (DHF). The total number of DF cases was 28.50% (57/200) and number of DHF cases was 71.50% (143/200). The patients of DHF group were found to have more liver derangement that is 90.20% (128/200) while the patients belonging to DF group were at a less risk for impairment of liver function that is 9.80% (15/200). The patients with dengue hemorrhagic fever are more prone to have liver enzyme derangement and it has a direct relation with the titer IgM in the body of patients infected with dengue virus. The liver enzyme which are found to be more raised are serum ALT and AST while serum alkaline phosphatase and serum bilirubin are not markedly raised.